Merevolusi Pendidikan dengan Kecerdasan Buatan Chatbots: Meningkatkan Pembelajaran dan Penilaian - Qurratul A'ini; Rosyidatul Khoiriyah (LP2M Universitas Ibrahimy, 2024)
This study explores the integration of AI chatbots in education to enhance learning and assessment. Focusing on their implementation in classroom teaching and small-scale scientific inquiry activities, the research aims to improve interactions between teachers and students by introducing new learning topics, methods, and providing feedback. The study involved 18 participants 11 fifth-grade and 7 sixth-grade students from a university-run science talent program. Findings highlight benefits such as increased engagement, personalized learning experiences, and automated assessment capabilities. Examples from language learning, mental health support, and academic advising illustrate chatbots' versatility in education. Overall, AI chatbots have the potential to transform education by offering tailored learning experiences, enhancing student engagement, and facilitating efficient assessment. The study suggests further exploration of chatbots' role in promoting student initiative within scientific inquiry learning.